What is the influence of tonsillectomy on the level of periodontal pathogens on the tongue dorsum and in periodontal pockets - V. N. Diener; A. Gay; M. B. Soyka; T. Attin; P. R. Schmidlin; P. Sahrmann (BMC, 2018)
Abstract Background For periodontal treatment, the full mouth disinfection approach suggests disinfection of oral soft tissues, such as tongue and tonsils concomitant to scaling and root planning since patients might benefit from treatment of these oral niches either. Periodontopathogenes in tonsillar tissue support this hypothesis. This prospective controlled clinical study investigated the change in the oral flora of patients who underwent tonsillectomy. Pockets were tested for eleven bacterial species before and six weeks after the surgical intervention. Methods Fifty generally healthy adults were included in this study. The test group consisted of 25 patients with tonsillectomy. The control group included 25 patients with otorhinolarynologic surgery without involvement of the oral cavity. Clinical parameters such as probing pocket depth, bleeding-on-probing index and plaque index were registered the evening before surgery. Also bacterial samples from the gingival sulcus and dorsum linguae were taken, and an additional sample from the removed tonsils in the test group. Six weeks after the intervention microbial samples of pockets and tongue were taken again. Data were tested for significant differences using Wilcoxon rank and Whitney-u-test. Results No relevant intra- or intergroup differences were found for the change of the eleven investigated species. Conclusion Based on the results of the present study, tonsillectomy does not seem to have an immediate relevant effect on the bacterial flora of tongue or periodontium. This study design was approved by the ethical committee of Zurich (KEK-ZH-Nr.2013-0419). Trial registration The trial was retrospectively registered in the German Clinical Trials Register (DRK00014077) on February 20, 2018.